2010
DOI: 10.1016/j.nmd.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone induces dysferlin in myoblasts and enhances their myogenic differentiation

Abstract: Glucocorticoids are beneficial in many muscular dystrophies but they are ineffective in treating dysferlinopathy, a rare muscular dystrophy caused by loss of dysferlin. We sought to understand the molecular basis for this disparity by studying the effects of a glucocorticoid on differentiation of the myoblast cell line, C2C12, and dysferlin-deficient C2C12s. We found that pharmacologic doses of dexamethasone enhanced the myogenic fusion efficiency of C2C12s and increased the induction of dysferlin, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 58 publications
9
45
0
Order By: Relevance
“…Our results indicate that the effect of proteasomal inhibition is largely due to the interference with the degradation of missense mutated dysferlin rather than due to the enhanced dysferlin mRNA expression. This is in line with a recent study (18) in which a 10-fold increase in dysferlin mRNA obtained by dexamethasone treatment of C2C12 myoblasts was able to only double dysferlin protein levels. The above observations, therefore, suggest that the markedly increased levels of mis-sense mutated dysferlin in our study are largely due to the inhibition of protein degradation, although we cannot exclude that the slight increase in dysferlin mRNA, through as yet unexplored mechanisms, may also play a role.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that the effect of proteasomal inhibition is largely due to the interference with the degradation of missense mutated dysferlin rather than due to the enhanced dysferlin mRNA expression. This is in line with a recent study (18) in which a 10-fold increase in dysferlin mRNA obtained by dexamethasone treatment of C2C12 myoblasts was able to only double dysferlin protein levels. The above observations, therefore, suggest that the markedly increased levels of mis-sense mutated dysferlin in our study are largely due to the inhibition of protein degradation, although we cannot exclude that the slight increase in dysferlin mRNA, through as yet unexplored mechanisms, may also play a role.…”
Section: Discussionsupporting
confidence: 93%
“…These contradictory effects of GC on myogenesis may reflect a concentration-dependent biphasic response. Belanto et al (2), for example, observed increased myoblast fusion in response to low GC levels, and we postulate that those results could be derived from an interaction between GC and anabolic factors, like IGF-I, present in the cell culturing serum. This notion is in line with the synergistic stimulation of myotube formation in response to simultaneous addition of GC and IGF-I during myoblast differentiation reported here and suggests that independent mechanisms lie at the basis of inhibition of myoblast fusion by GC and its synergistic stimulation when combined with IGF-I.…”
Section: Discussionsupporting
confidence: 54%
“…We and others previously demonstrated segregation between morphological and biochemical parameters of myogenic differentiation (2,3,33). However, the abundance of musclespecific and particularly MHC proteins was consistently increased in the presence of IGF-I/GC compared with IGF-I only, indicating that the regulatory cues in control of both muscle-specific gene expression and myoblast fusion corresponded.…”
Section: Discussionmentioning
confidence: 65%
“…20,22 In contrast, the administration of 5-25 nM DEX has improved myogenesis in vitro by enhancing differentiation and myotube fusion of myogenic murine cells, potentially through its induction of dysferlin, a calcium-binding transmembrane protein thought to play a key role in both myogenesis and membrane repair. 23 Similar studies have demonstrated that DEX can inhibit protein synthesis and myoblast proliferation in vitro, 24 however, reinforcing the need for careful timing of addition to culture.…”
mentioning
confidence: 90%